Judicial Purpose and the Scholarly Process: The Lincoln Mills Case - James E. Pfander (Washington University Law Quarterly, 1991)
This Article revisits the debate between Douglas and Frankfurter with a view towards assessing the merits of the two Justices' competing interpretations of section 301. Part I traces the origins of the Taft-Hartley Act and the likely attitudes of Douglas and Frankfurter towards legislation that was meant to curtail the power of trade unions by giving federal courts a larger role in policing industrial conflict. I show that Frankfurter was deeply committed to the notion that federal courts were institutionally unfit to play such a role. Next, I review in greater detail the opinions in the Lincoln Mills case and their reception by labor law scholars, who largely accepted the central claim of Frankfurter's dissent: Congress intended section 301 to solve the procedural problems that employers experienced in attempting to enforce the collective bargain in state court and merely to confer jurisdiction on the federal courts to hear such claims. In Part II of the Article, I conduct a review of the language, structure, and history of the statute. In sharp contrast to the conventional wisdom, such a review discloses an array of evidence supporting Douglas's conclusion that section 301 not only established a federal substantive right to contract enforcement, but also authorized the federal courts to fashion rules to govern actions to enforce collective bargaining agreements on a case-by-case basis. I begin by reviewing the state court enforcement difficulties that led to the statute's passage. I show that most state courts enforced the collective contract, if at all, by relying on the individual contract of hire between employees and the firm. Section 301 addresses the resulting enforcement difficulties by transforming the contract enforcement action from a suit brought to vindicate individual rights into an action to enforce collective or group interests; the statute made both unions and employers responsible for their labor contracts on a collective or entity basis. These substantive changes in labor contract enforcement theory belie any claim that section 301 incorporated state law; indeed, the debates and committee reports assume that violations of labor contracts would present a federal question. Such was the position of the principal sponsor and draftsman of the statute, Senator Robert Taft, who defended section 301 from the precise constitutional attack that Frankfurter later mounted on the statute by expressly rejecting the claim that section 301 contemplated reference to state substantive law. While this evidence suggests that the judicial power recognized in Lincoln Mills rests on more than the historical accident that Justice Douglas had five votes for his reading of section 301, it raises more complex questions. In view of the statute's substantive content, it appears difficult to understand why Douglas failed to offer more cogent support for his interpretation of the statute, why Frankfurter was moved to attack section 30 I's constitutionality, and why the legitimacy of the judicial role the statute envisioned has been so widely questioned. This Article addresses these questions in Part III. It concludes that the conventional understanding of section 301 rests on a conviction, shared by Frankfurter and many students of industrial relations, that the courts should stay out of industrial relations.
Keywords: Collective bargaining; Judicial review; Textile Workers Union v. Lincoln Mills; 77 S. Ct. 912